Novel Co‐Catalytic Activities of Solid and Liquid Phase Catalysts in High‐Rate Li‐Air Batteries. Issue 45 (13th October 2022) - Zhang, Chengji; Jaradat, Ahmad; Singh, Sachin Kumar; Rojas, Tomas; Ahmadiparidari, Alireza; Rastegar, Sina; Wang, Shuxi; Majidi, Leily; Redfern, Paul; Subramanian, Arunkumar; Ngo, Anh T.; Curtiss, Larry A.; et al.
Abstract: Li‐air batteries are considered strong candidates for the next‐generation energy storage systems designed for electrical transportation. However, low cyclability and current rates are two major drawbacks that hinder them from further realization. These issues necessitate the discovery of novel materials to significantly enhance the redox process of discharge products. In this study, a novel catalytic system comprised of tin sulfide (SnS) nanoflakes as a solid catalyst and tin iodide (SnI2 ) as a dual‐functional electrolyte additive is discovered. This system enables operating the battery at high current rates up to 10 000 mA g −1 (corresponding to 1 mA cm −2 ). The SnS catalyst shows outstanding catalytic activity for both oxygen reduction and evolution reactions compared to carbon, noble metals, and other transition metal dichalcogenides. It also exhibits good structural integrity at high rates. The computations indicate numerous possible oxygen reduction sites without oxygen dissociations on the SnS surface through solution mechanism that is likely responsible for the formation of Li2 O2 . The calculations also indicate that the role of the SnI2 is not only reacting with the lithium anode to provide protection but reducing the charge potential by promoting catalytic decomposition of the Li2 O2 . This work provides new novel additives for designing high‐rate Li‐air batteries. Abstract : A new novel solid state catalyst and bi‐functional electrolyte additive system is reported, which enables Li‐air batteries to operate at high‐rate up to 1 mA cm −2 for many cycles. Further investigations and density functional calculations are carried out to provide fundamental understanding of the working mechanism, electrochemical catalysis, and long‐term durability of this co‐catalytic system in high‐rate Li‐air batteries.